Development and characterization of protein-rich cookies fortified with red kidney beans: A nutritional approach to combat malnutrition - Zahid, Tehreem; Nooreen, Saba; Asif, Muhammad; Maqsood, Sammra; Saddiqa, Ayesha; Naqvi, Syeda Noor ul Ain; Nazar, Mishal; Alvi, Tayyaba; Rafiq, Mehwish (Journal of Pure and Applied Agriculture, 2025)
Malnutrition is a severe issue in developing countries due to the rapidly growing population, urbanization and industrialization, and a reduction in agricultural lands. It ultimately is an alarming situation for food security, thus, there is a need to look for alternate sources for food and nutrition security. This work aimed to enhance the compositional and functional properties of the cookies. In this study, different concentrations (0, 3, 6, 9, 12%) of red kidney beans were used to prepare cookies (T0, T1, T2, T3 and T4). Nutritional, functional and sensorial attributes were assessed. Results showed that the inclusion of red kidney beans in cookies increased the protein and crude fiber contents by 1.75 and 1.40 times, respectively than the control sample. Functional properties of cookies such as water holding capacity and oil holding capacity were significantly increased (P<0.05). However, bulk density and water absorption capacity of cookies were significantly decreased (p<0.0%). Dietary fiber and mineral composition (iron, phosphorus, calcium and magnesium) in cookies significantly improved (p<0.05). Moreover, the sensorial attributes indicated that adding 9% red kidney beans to cookies was acceptable. In short, the addition of red kidney beans in cookies may help to mitigate malnutrition.